Legal Responses to Vacant Houses An International Comparison - Kadomatsu, Narufumi; Kelly Jr., James J.; Melot, Romain; Pilniok, Arne.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book presents an international comparison of legal responses to the issue of vacant housing in Japan, the USA, France and Germany. While vacant housing is a shared problem in these four countries, the origin and context of the problem, as well as the focus of legal responses, differ considerably. Presenting the outcomes of an international symposium, this book explores different legal approaches (private/public law, federal/national/municipal governments, demolition/expropriation/requisition/planning) taken in the respective jurisdictions. It is highly recommended to readers whose work involves practical issues concerning vacant housing and who are interested in theoretical aspects of property law, building law and administrative law. The book also includes a chapter exploring the implications of the (3z(Btragedy of the commons/anticommons(3y (Bfor contemporary land use issues in Japan such as landscape protection, area management and unclaimed land. .s
Introduction -- Chap.1 Emergence of Unoccupied House Problem in Japan and Legal Measures towards This Issue -- Chap.2 Municipal Responses to Vacant Properties in the United States -- Chap.3 Expropriation of Vacant Property in France: the Case of Substandard Housing -- Chap. 4 The Urban Planning Development Concept as a Central Instrument for Managing Apartment Vacancies in German Law -- Chap.5 The Tragedies of the Commons and Anticommons in an Era of Underuse.
Keywords: Property; Private international law; Conflict of laws; Administrative law; Common Property and Land Law; Private International Law, International & Foreign Law, Comparative Law .; Administrative Law